A Comparative Antimicrobial Study of Deepika Rasa Prepared by two Different Methods (AYUSHDHARA, 2022)
The Indian classic of Rasashastra have contribute numerous Rasayoga for various disease. In modern era for the development of Ayurvedic medicine with the proof scientifically and use of new search antibiotics to be increase, Deepika rasa is not popular traditional medicine so an attempt has been made to develop a safe & less expensive antimicrobial drug. Deepika rasa formulations are selected for the present study from Rasa Ratan Samuccaya (U.K.A12). Deepika rasa was indicated as “Sarva Jwarhar Vinashanam”. Deepika rasa is one among Kharaleeya Kalpana. In this study we prepared Deepika rasa by two different methods: 1. Deepika rasa formulation- Rasa Ratan Samuccaya (U.K.A.) [D1] 2. Deepika rasa formulation- Modified method [D2]. The difference between above formulations was that Rasa Sindoora was used in the place of Parad and Gandhak in the formula two of Deepika rasa. This was because of the preparation Rasa sindoora was more potent as compared to Kajjali of first formula. The above said formulations were subjected to antimicrobial investigations to determine their quality, standards and anti-microbial effects on 5 pathogenic bacteria strain Streptococcus pyogenes, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, and Salmonella typhi. These pathogens are very common for fever. In order to study antibacterial action of Deepika rasa in vitro well diffusion method. During this study Deepika rasa was trailed with bacterial at different concentration. To correlate the result control solution were prepared by streptomycin. Experimental group were compared with control group and observations were noted. The encouraging results obtained from anti-microbial study of both sample of Deepika rasa. Deepika rasa 1 & Deepika rasa 2 was highly significant for some pathogen with the different concentration and moderately significant for some pathogen with the different concentration and no significant for some pathogen with the different concentration. So an attempt was made to find a safe and effective Ayurvedic medicine.